2009
DOI: 10.1109/tit.2008.2009815
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Graph Codes That Are Optimal for Binning and Coding With Side Information

Abstract: Abstract-In this paper, we describe and analyze the source and channel coding properties of a class of sparse graphical codes based on compounding a low-density generator matrix (LDGM) code with a low-density parity-check (LDPC) code. Our first pair of theorems establishes that there exist codes from this ensemble, with all degrees remaining bounded independently of block length, that are simultaneously optimal for both channel coding and source coding with binary data when encoding and decoding are performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 61 publications
(173 reference statements)
1
58
0
Order By: Relevance
“…We name the codes HsuAnastasopoulos (HA) codes after the inventors. Furthermore, Wainwright and Martinian showed HA codes achieve the rate-distortion bound for symmetric Bernoulli sources [23].…”
Section: K2mentioning
confidence: 99%
“…We name the codes HsuAnastasopoulos (HA) codes after the inventors. Furthermore, Wainwright and Martinian showed HA codes achieve the rate-distortion bound for symmetric Bernoulli sources [23].…”
Section: K2mentioning
confidence: 99%
“…In this respect, Matsunaga and Yamamoto [5] showed that if the degrees of a low-density parity-check (LDPC) ensemble are chosen as large as Θ(log(N )), where N is the blocklength, then this ensemble saturates the ratedistortion bound if optimal encoding is employed. Even more promising, Martininian and Wainwright [6] proved that properly chosen MN codes with bounded degrees are sufficient to achieve the rate-distortion bound under optimal encoding.…”
mentioning
confidence: 99%
“…Since portions of this research were first published in conference form [46], [29], other work has followed up and extended some of our results. Martinian and Wainwright [30], [31], [47] have studied the use of compound constructions, in which an LDGM code is concatenated with an LDPC code, for both lossy compression and binning. Gupta and Verdu [21] have used similar analysis techniques (moment methods) to study the performance of a novel non-linear scheme for lossy compression.…”
mentioning
confidence: 99%